Akibat Hukum Penyalahgunaan Pemakaian Kosmetik Berbahan Kimia Dengan Edar Palsu Dan Tidak Mencantumkan Nomor Badan Pengawas Obat Dan Makanan (BPOM) (Studi di Pasar Simpur Bandar Lampung) - Haqkiki Bintang Pratama; Zainudin Hasan; Adelya Putri Utami; Figo Putra Ranenda (International Forum of Researchers and Lecturers, 2023)
Society's need for cosmetics has led to the emergence of many cosmetic manufacturers. Distribution permits to sell freely on the market currently do not have many cosmetic products. The purpose of this research is to find out the legal consequences of the abuse of chemical-based cosmetics that do not include the number of the Food and Drug Supervisory Agency (BPOM) with counterfeit distribution (study center at Pasar Simpur, Bandar Lampung). The legal consequence of the abuse of the use of chemical-based cosmetics that are not listed as BPOM numbers with counterfeit distribution (Study Center in Bandar Lampung's Simpur Market), can be subject to various statutory provisions, namely Law Number 36 of 2009 concerning Health, Law Number 8 of 2011 concerning Protection Consumers and Decision of the Head of BPOM Republic of Indonesia Number HK 00.05.4.1745 The sanctions obtained consist of administrative sanctions and criminal sanctions.